2012
DOI: 10.1167/12.13.7
|View full text |Cite
|
Sign up to set email alerts
|

Holistic processing as a hallmark of perceptual expertise for nonface categories including Chinese characters

Abstract: Holistic processing has been associated with perceptual expertise in different domains involving faces, cars, fingerprints, musical notes, English words, etc. Curiously Chinese characters are regarded as an exception, as indicated by reduced holistic processing found for experts with the Chinese writing system as compared with novices. We revisit the issue and examine one type of holistic processing, the obligatory attention to all parts of an object, using the composite paradigm from face perception literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 74 publications
8
84
0
Order By: Relevance
“…Consistent with this domain-general account, composite effects obtained using the complete design have been reported for non-face objects of expertise encountered naturally, including cars (Bukach, Phillips, & Gauthier, 2010;Gauthier, Curran, Curby, & Collins, 2003), words (A. C. Wong et al, 2011), Chinese characters (A. C. Wong et al, 2012), and chess boards (Boggan, Bartlett, & Krawczyk, 2012). Similar composite effects have been reported with synthetic non-face objects, including 'Greebles' (Gauthier & Tarr, 2002;Gauthier, Williams, Tarr, & Tanaka, 1998) and 'Ziggerins' (A. C. Wong et al, 2009), where expertise is acquired through lab-based training.…”
Section: Domain Specific Vs Domain General Processingsupporting
confidence: 54%
“…Consistent with this domain-general account, composite effects obtained using the complete design have been reported for non-face objects of expertise encountered naturally, including cars (Bukach, Phillips, & Gauthier, 2010;Gauthier, Curran, Curby, & Collins, 2003), words (A. C. Wong et al, 2011), Chinese characters (A. C. Wong et al, 2012), and chess boards (Boggan, Bartlett, & Krawczyk, 2012). Similar composite effects have been reported with synthetic non-face objects, including 'Greebles' (Gauthier & Tarr, 2002;Gauthier, Williams, Tarr, & Tanaka, 1998) and 'Ziggerins' (A. C. Wong et al, 2009), where expertise is acquired through lab-based training.…”
Section: Domain Specific Vs Domain General Processingsupporting
confidence: 54%
“…Other research suggests a reduced role of some kinds of information for nonface objects [Gauther and Tann 1997;Wong et al 2012a;Tan and Poggio 2013]. We predict that configural information such as the distances between object parts may be relatively less important for realism judgments of nonface objects as compared to realism judgments of faces.…”
Section: Generalization To Objectsmentioning
confidence: 56%
“…Holistic processing may be a general marker of expertise across a wide domain of visual discrimination [Wong et al 2012a]. In neuroscience, some experimental evidence supports the idea that face perception shares brain areas with object perception [Moscovitch et al 1997;Rossion et al 2002;Xu 2005;McKeeff et al 2010;Rossion et al 2012;Goffaux et al 2013] and that the functional overlap between face and object perception is increased by expertise [McKeeff et al 2010].…”
Section: Generalization To Objectsmentioning
confidence: 99%
“…Part-based face processing demonstrates the tendency to process facial information individually, in a feature-by-feature manner. Studies have shown that normally-developed individuals process faces and face-like stimuli holistically (Young et al, 1987; Tanaka and Farah, 1993; Moscovitch et al, 1997; Tanaka et al, 1998; Maurer et al, 2002; Le Grand et al, 2004; Michel et al, 2006; Schwarzer et al, 2007; Richler et al, 2008, 2011a; Wang et al, 2012; Wong et al, 2012). Holistic face processing is primary for upright human face stimuli, but its use is greatly reduced for processing objects, inverted faces, or upright faces from another ethnic background (Michel et al, 2006; McKone et al, 2007, 2013; McKone, 2008).…”
Section: Facial Movements Optimize Face Processingmentioning
confidence: 99%